2020
DOI: 10.21203/rs.3.rs-122944/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic Maternal Hepatitis B Virus Infection and Pregnancy Outcome - A Single Center Study in Kunming, China

Abstract: Background: Chinese population has a high prevalence of chronic hepatitis B virus (HBV) infection, the impact of which on pregnancy outcome remains controversial. A single-center retrospective cohort study was performed in Kunming, a multi-ethnic city in south-western China to examine this issue. Methods: The singleton pregnancies delivering at ≥28 weeks gestation under our care in 2005-2017 constituted the study cohort. Maternal characteristics and pregnancy outcome were compared between mothers with and wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 33 publications
1
7
2
Order By: Relevance
“…In this study, we investigated the outcomes of 735 pregnant women with HBsAg carrier status and 18 693 cases in a nonexposed group of subjects in Hangzhou, China. We found that the proportion of positive maternal HBsAg carrier was 3.78%; this was slightly higher than the 3.3% rate reported previously in Kunming, China [18]. In China, people such as medical staff, nursery staff, patients receiving organ transplants, people frequently accessible to blood transfusions, blood products or intravenous drug, people with poor immunity or vulnerable to trauma, people with multiple sexual partners or with family members of HBsAg-positive, etc., are under high risk of hepatitis B [19].…”
Section: Discussioncontrasting
confidence: 58%
“…In this study, we investigated the outcomes of 735 pregnant women with HBsAg carrier status and 18 693 cases in a nonexposed group of subjects in Hangzhou, China. We found that the proportion of positive maternal HBsAg carrier was 3.78%; this was slightly higher than the 3.3% rate reported previously in Kunming, China [18]. In China, people such as medical staff, nursery staff, patients receiving organ transplants, people frequently accessible to blood transfusions, blood products or intravenous drug, people with poor immunity or vulnerable to trauma, people with multiple sexual partners or with family members of HBsAg-positive, etc., are under high risk of hepatitis B [19].…”
Section: Discussioncontrasting
confidence: 58%
“…Nevertheless, a number of other studies [18][19][20][21][22][23][24][25][26][27][28] did not demonstrate such an association. The reasons for the conflicting findings have not been elucidated, but several factors could be involved.…”
Section: Gdmmentioning
confidence: 88%
“…Paradoxically, HBV carriage also appears to confer some reproductive advantage in form of reduction in hypertension in pregnancy, especially PE, as well as enhanced fetal growth manifesting as reduction in LBW/SGA infants, and increase in birthweight as well as LGA and macrosomic infants. Indeed, a significant proportion of the studies found no or minimally increased adverse obstetric outcome in HBV carriers, and it was suggested that chronic HBV infection may have evolved to become synergistic with human reproduction in order to facilitate its transmission down successive human generations to perpetuate the infection in its primary host [28]. Most of the available studies on this topic are retrospective and are limited in the available information especially regarding the mechanisms or explanations involved in the association between chronic HBV infection with various reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations